Penerapan Authentic Assesment Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Ma’arif 1 Karangbinangun Lamongan - Miftakhul Muthoharoh (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, Changes in educational paradigms that initially made teachers as actors and instructors turned into facilitators and motivators. This paradigm shift has also become a reference for curriculum changes, and currently the curriculum developed by the government is the 2013 curriculum. This curriculum is a curriculum loaded with efforts to shape the character of learners and also competence, in practice to achieve the curriculum objectives assessment is an important aspect must be done as a way of measuring student learning outcomes, and Authentic Assessment is the thing that is emphasized in the implementation of the 2013 curriculum. Therefore, every education unit must strive to implement this Authentic Assessment in order to get a comprehensive value between the value of knowledge, attitudes and skills.Keywords: authentick, assessment, assessment, authentic, and Islamic religious education